(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
Lope de Vega wrote two plays about episodes related to the wars in Chile in the so-called Arauco territory: the eucharistical play, La Araucana, and the tragicomedy Arauco Domado. Both are very different from the homonymous epic poems written by Ercilla and Oña, respectively. This paper attempts to deal with the images Lope constructed about of the Arauco territory and the Araucanians as well as the verbal resources he used to portray such contents to the people of this time.